Angola : IMF Concludes 2003 Article IV Consultation with Angola; 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2003)
The ending of the civil war has brought to the fore the need to reconstruct the Angolan economy and address the problem of widespread poverty. A strong medium-term fiscal adjustment effort, including a reduction of the National Bank of Angola's operational deficit, is needed. The government should pursue a much more prudent foreign borrowing policy to avoid a worsening of the external debt burden. A tighter macroeconomic policy accompanied by a decisive structural reform is needed to foster economic diversification, create employment opportunities, and increase productivity.